FAKTOR-FAKTOR PENYEBAB PRAKTIK NIKAH SIRI DI DESA CIBUNTU KECAMATAN CIBITUNG - Qurrotul Ayuni; Yoyo Hambali; Suprihatin Suprihatin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2023)
This study aims to determine the factors of unregistered marriage in the Cibuntu village community, Cibitung sub-district. This type of research is qualitative research with field research. Data sources are Primary Materials, namely data sources directly obtained from informants who are the perpetrators of unregistered marriages in Cibuntu Village, then secondary materials, namely books related to research issues, journals, etc. Data collection techniques using interviews and documentation and data analysis techniques using qualitative analysis. Factors that cause unregistered marriages in Cibuntu village, Cibitung sub-district, namely economic factors, pregnancy out of wedlock, underage marriage, parental concerns and lack of knowledge and understanding of the community about the importance of registering marriages. Of the six factors, economics is the most dominant reason for unregistered marriage.